Influence of spacing in the upper lateral incisor area on the perception of smile esthetics among orthodontists and laypersons - Machado, Andre Wilson; Moon, Won; Campos, Edson Alves de [UNESP]; Gandini, Luiz Gonzaga [UNESP] (Elsevier, 2013)
Background: The aim of this study was to determine the perception of smile esthetics among orthodontists and laypeople with respect to the presence of diastemas in the upper lateral incisor in the mesial, distal, and both surfaces using an oblique smile analysis. Methods: Two standardized oblique photos of pleasant smiles from two white women were selected. Images were digitally altered to create diastemas in the lateral incisor, in 0.5-mm increments, in the mesial, distal, or both surfaces. Final images were randomly assembled in a photo album, which was given to 120 judgesd60 orthodontists and 60 laypersons. Each rater was asked to evaluate the attractiveness of the images on a visual analog scale. The data collected were submitted to statistical analysis by the means of one-way ANOVA with the Tukey post hoc test and the unpaired Student’s t test. Results: The most attractive smile was the one without spacing, and the presence of diastemas was considered unattractive by both groups of raters, following a pattern: the greater and the more mesially located, the more unattractive was the smile. Conclusions: The results of this study suggest that diastemas in the upper lateral incisor area were considered unattractive, following a pattern: the greater and the more mesially located, the more unattractive was the smile.
Keywords: Cosmetic dentistry; Diastemas; Orthodontics; Smile esthetics